Censorship detected in KH (Cambodia) - Voidly (Voidly Global Censorship Index, 2025)
WARNING severity censorship detected in Cambodia. Data sourced from CensoredPlanet.
Censorship Incident ID: KH-2025-0001. Severity: warning. Confidence: 75%